Dynamics of yardstick regulation: Historical cost data and the ratchet effect - Johannes Meya (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
Real life applications of yardstick regulation frequently refer to historical cost data. While yardstick regulation cuts the link between firms own costs and prices firms may charge in a static setting, it does not do so in a dynamic setting where historical cost data is used. A firm can influence the price it will be allowed to charge in the future if its behavior today can affect future behavior of other firms that determines the price this firm will be able to charge later on. This paper shows that, assuming that slack, inflation of costs, is beneficial to firms, a trade-off between short term profit through abstinence from slack in (infinitely) many periods arises. A ratchet effect that yardstick regulation was meant to overcome can occur and firms can realize positive rents because of the use of historical cost data, even if firms are identical. Equilibria with positive slack can exist without any collusion between firms or threat. Moreover, this problem is more severe if the firm with lowest costs of all other firms instead of the average firm is the yardstick.
Keywords: L51; L98; C73; 330; yardstick regulation; yardstick competition; ratchet effect; historical cost data